2010
DOI: 10.1158/0008-5472.can-09-2833
|View full text |Cite
|
Sign up to set email alerts
|

Talin1 Promotes Tumor Invasion and Metastasis via Focal Adhesion Signaling and Anoikis Resistance

Abstract: Talin1 is a focal adhesion complex protein that regulates integrin interactions with ECM. This study investigated the significance of talin1 in prostate cancer progression to metastasis in vitro and in vivo. Talin1 overexpression enhanced prostate cancer cell adhesion, migration, and invasion by activating survival signals and conferring resistance to anoikis. ShRNA-mediated talin1 loss led to a significant suppression of prostate cancer cell migration and transendothelial invasion in vitro and a significant i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
176
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(183 citation statements)
references
References 38 publications
5
176
1
1
Order By: Relevance
“…A recent study showed that the regulation of talin levels by overexpression or siRNA silencing greatly affects prostate cancer cell migration and invasion (45). Because we identified talin as an intracellular CtsH target in PC-3 cells, we propose that CtsH could regulate prostate cancer cell migration by cleaving talin.…”
Section: Discussionmentioning
confidence: 81%
“…A recent study showed that the regulation of talin levels by overexpression or siRNA silencing greatly affects prostate cancer cell migration and invasion (45). Because we identified talin as an intracellular CtsH target in PC-3 cells, we propose that CtsH could regulate prostate cancer cell migration by cleaving talin.…”
Section: Discussionmentioning
confidence: 81%
“…3C). Thus, PHIP can regulate the expression of upstream mediators of the IGF axis and downstream mediators of tumor cell invasion (8).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, microarray analysis revealed down-regulation of Tln1 in melanoma cells with reduced Phip expression. TLN1, which is involved in the assembly of actin filaments, has been shown to mediate tumor invasion and metastasis through AKT-dependent effects (8). in which PHIP directs a coordinated program of melanoma cell invasion through the activation of TLN1 and AKT.…”
Section: Discussionmentioning
confidence: 99%
“…For example, caveolin-1 promotes metastasis of bladder cancer through a pharmacologically tractable common downstream signaling pathway and has been further researched for personalized therapy to suppress metastases (Thomas et al, 2011). Talin1 overexpression enhances cancer cell adhesion, migration, and invasion by activating survival signals and conferring resistance to anoikis (Sakamoto et al, 2010). Other examples are adenylate cyclase-associated protein 1 and human fatty acid synthase (Yamazaki et al, 2009;Shao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%